RELATIONSHIP BETWEEN THE PERCEPTION OF THE ROLE OF FATHER WITH INTERPERSONAL COMPETENCE IN STUDENTS AT FRANSISKUS JUNIOR HIGH SCHOOL SEMARANG - Anggun Lembah Sari; Achmad Mujab Masykur (Faculty of Psychology, Diponegoro University, 2013)
Interpersonal competence supports academic achievement and success in business, so that students are required to have adequate interpersonal competence. Meanwhile, the phenomenon shows the many social problems faced by teenagers, such as delinquency and criminality in adolescents, which showed inadequate interpersonal competence. This study aims to determine the relationship between perceptions of the role of fathers with interpersonal competencies in students. The research hypothesis is that there is a positive relationship between perceptions of the role of fathers with interpersonal competencies in students.The subjects were students of class VII-VIII Fransiskus Junior High School Semarang obtained by cluster random sampling. Data were obtained using the Interpersonal Competence Scale and the Perceptions of Role of Fathers in Student Scale, and then analyzed using simple regression analysis.The result is a positive relationship between perceptions of the role of fathers with interpersonal competencies in students. The more positive perception of the role of the father, the higher the students' interpersonal competence, and vice versa. Perceptions of the role of fathers the influence on interpersonal competencies in students by 39%.